1999
DOI: 10.3168/jds.s0022-0302(99)75448-2
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Catabolism by Lactobacillus casei and Lactobacillus helveticus Cheese Flavor Adjuncts

Abstract: Microbial degradation of Trp is thought to promote the formation of aromatic compounds that impart putrid, fecal, or unclean flavors in cheese, but pathways for their production have not been established. This study investigated Trp catabolism by Lactobacillus casei and Lactobacillus helveticus cheese flavor adjuncts under carbohydrate starvation (pH 6.5, 30 or 37°C, no sugar) and near cheese-ripening (pH 5.2, 4% NaCl, 15°C, no sugar) conditions. Enzyme assays of cell-free extracts indicated that both species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…Transamination is a common theme in amino acid biochemistry, and while many of these enzymes exhibit some degree of overlapping specificity, evolutionary pressure to retain several paralogs is more likely a reflection of individual enzyme specificity than gross functional redundancy. In any event, previous work has suggested that the "remnant" aminotransferases do contribute to amino acid breakdown by L. helveticus CNRZ 32 (8,9) and that the ␣-keto acids generated by these enzymes may, depending on enzyme activity and substrate availability, be further catabolized by other bacteria present in cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Transamination is a common theme in amino acid biochemistry, and while many of these enzymes exhibit some degree of overlapping specificity, evolutionary pressure to retain several paralogs is more likely a reflection of individual enzyme specificity than gross functional redundancy. In any event, previous work has suggested that the "remnant" aminotransferases do contribute to amino acid breakdown by L. helveticus CNRZ 32 (8,9) and that the ␣-keto acids generated by these enzymes may, depending on enzyme activity and substrate availability, be further catabolized by other bacteria present in cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the Phe catabolites phenylacetaldehyde and 2-phenethyl alcohol have been shown to impart floral, rose-like off-flavors, and the Tyr catabolite p-cresol imparts barny, medicinal, or utensil-like offflavors (15,22,32). Mechanisms for the production of these compounds in cheese have not been conclusively established, but AAA catabolism by lactococci and lactobacilli under simulated cheese-ripening conditions is initiated by aminotransferase (ATase) enzymes that convert AAAs into corresponding ␣-keto acids (17,20,21,39). Moreover, the aromatic ␣-keto acids produced by these reactions can be nonenzymatically converted to benzaldehyde, phenylacetaldehyde, 2-phenethyl alcohol, and other aroma compounds (17,19,20,21,38).…”
mentioning
confidence: 99%
“…Mechanisms for the production of these compounds in cheese have not been conclusively established, but AAA catabolism by lactococci and lactobacilli under simulated cheese-ripening conditions is initiated by aminotransferase (ATase) enzymes that convert AAAs into corresponding ␣-keto acids (17,20,21,39). Moreover, the aromatic ␣-keto acids produced by these reactions can be nonenzymatically converted to benzaldehyde, phenylacetaldehyde, 2-phenethyl alcohol, and other aroma compounds (17,19,20,21,38). However, many lactic acid bacteria possess hydroxy acid dehydrogenases (HADH) such as D-hydroxyisocaproic acid dehydrogenase (D-Hic) that convert ␣-keto acids to ␣-hydroxy acids (7,23), and these enzymes are active in cells incubated under cheese-ripening conditions (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the amino acid catabolic pathways in the different bacteria present in these cheeses are not well known. This knowledge could lead to the development of cultures with optimized aromatic properties.Amino acid catabolism by Lactococcus lactis and mesophilic lactobacilli has been extensively studied recently (2,8,11,19,26; S. Gummalla and J. R. Broadbent, Abstract, J. Dairy Sci.…”
mentioning
confidence: 99%